OLD family nuclease function across diverse anti-phage defense systems - Akritidou, Konstantina; Thurtle-Schmidt, Bryan H. (Frontiers in Microbiology, 2023)
Bacteriophages constitute a ubiquitous threat to bacteria, and bacteria have evolved numerous antiphage defense systems to protect themselves. These systems include well-studied phenomena such as restriction endonucleases and CRISPR, while emerging studies have identified many new anti-phage defense systems whose mechanisms are unknown or poorly understood. Some of these systems involve overcoming lysogenization defect (OLD) nucleases, a family of proteins comprising an ABC ATPase domain linked to a Toprim nuclease domain. Despite being discovered over 50 years ago, OLD nuclease function remained mysterious until recent biochemical, structural, and bioinformatic studies revealed that OLD nucleases protect bacteria by functioning in diverse anti-phage defense systems including the Gabija system and retrons. In this review we will highlight recent discoveries in OLD protein function and their involvement in multiple discrete anti-phage defense systems.